Association of pre and intraoperative variables with postoperative complications in coronary artery bypass graft surgery - Gimenes,Camila (2013)
OBJECTIVE: To associate the pre- and intraoperative variables with postoperative complications of patients undergoing coronary artery bypass graft surgery. METHODS: The pre- and intraoperative risk factors of individuals of both genders with diagnosis of coronary insufficiency undergoing coronary artery bypass graft have been studied. RESULTS: Fifty-eight individuals with median age 62 ± 10 year-old were included in the study, 67% of whom were male. Fourteen (24.1%) patients were smokers, 39 (67.2%) had previous myocardial infarction history, 11 (19%) had undergone coronary angioplasty, 74% had hypertension, 27% had diabetes mellitus, 64% had dyslipidemia and 15.5% had chronic obstructive pulmonary disease. Eighteen (31%) patients presented postoperative complications, most frequent being: infection in surgical incision, difficulties in deambulation, dyspnea, urinary infection and generalized weakness. Male patients had fewer complications than females (P=0.005). Patients with chronic obstructive pulmonary disease remained hospitalized for longer time periods (P=0.019). Postoperative complications occurred in 50% of the patients with creatinine increased, while only 27.1% of the patients with normal value of creatinine had complications (P=0.049). In addition, complications occurred in 50% of the patients with diabetes mellitus, while only 23.8% of patients without diabetes mellitus had complications (P=0.032). The intraoperative factors showed no statistically significant differences. CONCLUSION: The preoperative factors are associated with postoperative complications in patients undergoing coronary artery bypass graft surgery.